Shuni Virus Replicates at the Maternal-Fetal Interface of the Ovine and Human Placenta - Judith Oymans; Lucien van Keulen; Guus M. Vermeulen; Paul J. Wichgers Schreur; Jeroen Kortekaas (Pathogens, 2020)
Shuni virus (SHUV) is a neglected teratogenic and neurotropic orthobunyavirus that was discovered in the 1960s in Nigeria and was subsequently detected in South Africa, Zimbabwe, and Israel. The virus was isolated from field-collected biting midges and mosquitoes and shown to disseminate efficiently in laboratory-reared biting midges, suggesting that members of the families Culicidae and Ceratopogonidae may function as vectors. SHUV infections have been associated with severe neurological disease in horses, a variety of wildlife species, and domesticated ruminants. SHUV infection of ruminants is additionally associated with abortion, stillbirth, and congenital malformations. The detection of antibodies in human sera also suggests that the virus may have zoonotic potential. To understand how SHUV crosses the ruminant placenta, we here infected pregnant ewes and subsequently performed detailed clinical- and histopathological examination of placental tissue. We found that SHUV targets both maternal epithelial cells and fetal trophoblasts, that together form the maternal-fetal interface of the ovine placenta. Experiments with human placental explants, furthermore, revealed replication of SHUV in syncytiotrophoblasts, which are generally highly resistant to virus infections. Our findings provide novel insights into vertical transmission of SHUV in sheep and call for research on the potential risk of SHUV infection during human pregnancies.